Kekuatan Pengetahuan: Keutamaan Dan Manfaat Menjadi Orang Berilmu Dalam Qs. Fatir:28 (Kajian Tafsir Fi Zhilalil Qur’an) - Aini, Putri Rizki; Alfiansyah, Muhammad; Mahfi, Icha Alfira; Riantika, Putri Ayu (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2023)
Together with science, humans are carriers of the message of the caliphate on earth, which has an obligation to prosper and develop it. Islam is a comprehensive religion (overall). With knowledge, one's life will become more valuable and colorful. The religion of Islam highly values ​​people who are knowledgeable, because they see the importance of this knowledge. With knowledge a person will do everything that Allah subhanallahuwata'ala commands him and is afraid if he leaves something that He commands, while someone who is not knowledgeable will be swayed by the deception of his lust. The purpose of this paper is to reveal the meaning of the word Ulama as stated in QS. Fathir verse 28 which can be understood that scholars are not only in matters of religion but in other fields of knowledge can also be called scholars. The author conducts a study on the interpretation of the Fi Zhilalil Qur'an through collecting data obtained through qualitative methods, namely library research and using a phenomenological design, which will later produce descriptive data.